Pelaporan Statistik Structural Equation Modeling:Temuan dari Tiga Jurnal Bisnis - Didi Achjari (The Indonesian Journal of Accounting Research, 2013)
There are extensive sets of statistics in structural equation modelling, particularly the covariance-based one. Researchers, therefore, may or may not report all these statistics due to some reasons. This paper aims to investigate the way these sets of statistics are reported in business journals. Data were collected from three business journals since 1998 until June 2003 editions. As a result, sample consisted of 12 papers were obtained, which then was analysed in two phases. Firstly, they were analysed in terms of the comprehensiveness of model fit report. Secondly, the report of other important statistics was also assessed. To conclude, this study indicates these papers present statistics of the structural equation modelling in many ways. Further, the findings call for more attention toward appropriate statistical reporting in this regard.